Social inclusion gone wrong: the divisive implementation of the Temporary Protection Directive in Ireland - Zubareva, Anastasiia; Minescu, Anca (Frontiers in Social Psychology, 2024)
There were 96,338 Personal Public Service Numbers (PPSNs) given to people from Ukraine who arrived in Ireland under the Temporary Protection Directive (TPD) before October 2023. From the end of 2022 into 2023, there was also a rapid rise of far-right anti-refugee rhetoric in Ireland . We analysed how TPD policy, the Irish political discourse around it and its implementation through national institutions and local communities affected TPD beneficiaries and other groups in Ireland. This study used a combination of qualitative analysis of a governmental debate on the housing needs of TPD beneficiaries and ethnographic observations gathered while the authors worked to support the needs of TPD beneficiaries. We provide an explanation of how the TPD implementation in Ireland resulted in the social exclusion of its beneficiaries despite aiming for streamlined integration. In addition, the shortcomings in the TPD implementation had negative effects on different groups within Irish society. We use the 3N model - Narratives, Networks, and Needs to explain how the data and trends that we documented at different levels of analysis - national, intergroup and intragroup, and individual - were interconnected. This paper is focused on the first of the three studies in the ongoing research project and primarily addresses the Narratives (i.e., policy and its implementation, political discourse) while connecting them with some observed social inclusion/exclusion outcomes on the Networks and Needs dimensions. We explain how political Narratives influenced TPD implementation and the different actors involved in this process: public service providers, the general public, and TPD beneficiaries in Ireland. The uncoordinated implementation of accommodation provision led to serious disruptions of TPD beneficiaries’ Networks. This hindered individuals’ access to services which resulted in individual Needs remaining unmet. We also documented how racialised elements underlying the EU TPD contributed to exclusionary mechanisms within the TPD implementation in Ireland and how that created a double standard in service provision.